A RCT of telehealth for COPD patient's quality of life: the whole system demonstrator evaluation. (17th September 2015) - Rixon, Lorna; Hirani, Shashivadan P.; Cartwright, Martin; Beynon, Michelle; Doll, Helen; Steventon, Adam; Henderson, Catherine; Newman, Stanton P.
Abstract: Introduction/Objectives: Despite some concerns that the introduction of telehealth (TH) may lead to reductions in quality of life (QoL), lower mood and increased anxiety in response to using assistive technologies to reduce health care utilisation and manage long term conditions, this research focuses on the extent to which providing people with tools to monitor their condition can improve QoL. Methods: The Chronic Obstructive Pulmonary Disease (COPD) cohort of the Whole Systems Demonstrator Trial is a pragmatic General Practitioner (GP) clustered randomised controlled trial (RCT) evaluating TH in the UK from three regions in England. All patients at a participating GP practice were deemed eligible for inclusion in the study if they were diagnosed with COPD. Results: 447 participants completed baseline and either a short (4 months) or long term (12 months) follow‐up. There was a trend of improved QoL and mood in the TH group at longer‐term follow‐up, but not short term follow‐up. Emotional functioning ( g = 0.280 95%CI, 0.051–0.510) and mastery reached ( g = 2.979 95%CI, 0–0.46) significance at P < 0.05 (all Hedges g <0.3). Conclusions: TH showed minimal benefit to QoL in COPD patients who were not preselected to be at increased risk of acute exacerbations. Benefits were more likely in disease specific measures at longer term follow‐up. TH is a complex intervention and should be embedded in a service that is evidenced based. Outcome measures must be sensitive enough to detect changes in the target population for the specific intervention.